Analysis of Students' Mathematical Communication Skills Through Culturally Responsive Teaching and Differentiated Learning Based on Local Wisdom - Miptahul Pahmi; Mega Nur Prabawati (Jurnal Inovasi Pendidikan dan Sains, 2024)
This study aims to analyze students' mathematical communication skills in solving problems related to measures of central tendency in real-life contexts, focusing on the aspects of drawing, mathematical expression, and written text, as well as types of Newman’s errors. The analysis involved 25 students, with three selected as representatives based on their mathematical communication skill levels. The findings indicate that, on average, students exhibited a low level of errors across the three aspects, with average scores of 7.5 for drawing, 8.0 for mathematical expression, and 8.5 for written text. In the drawing aspect, students were able to present solutions visually well, although minor inaccuracies were noted. In the mathematical expression aspect, students understood the problems but tended to omit explicit solution steps. For the written text aspect, students often provided numerical results without formulating conclusions in sentence form. The main factors causing errors were a lack of habit in writing solution steps and conclusions, as well as a need for improved accuracy. A differentiated learning approach based on local wisdom positively contributed to reducing student error rates. However, strengthening practice in writing solution steps and composing conclusions is necessary to improve students' overall mathematical communication skills.